2021
DOI: 10.1302/2058-5241.6.210045
|View full text |Cite
|
Sign up to set email alerts
|

A guide to regional analgesia for Total Knee Arthroplasty

Abstract: Regional analgesia has been introduced successfully into the postoperative pain management after total knee arthroplasty, reducing pain scores, opioid use and adverse effects. Combination of regional analgesia techniques is associated with better pain management and lower side effects than single regional techniques. Adductor canal block provides good analgesia and considerably lower detrimental effect in muscular strength than femoral nerve block, enhancing surgical recovery. Infiltration techniques may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…No significant differences were found in functional test outcomes at any time point nor LOS. Most of the authors have also reported worse quadriceps strength preservation with the use of FNB [ 6 , 9 11 ]. However, different to us, some articles defended that FNB was associated with delayed functional recovery [ 6 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences were found in functional test outcomes at any time point nor LOS. Most of the authors have also reported worse quadriceps strength preservation with the use of FNB [ 6 , 9 11 ]. However, different to us, some articles defended that FNB was associated with delayed functional recovery [ 6 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the authors have also reported worse quadriceps strength preservation with the use of FNB [ 6 , 9 11 ]. However, different to us, some articles defended that FNB was associated with delayed functional recovery [ 6 , 11 , 12 ]. Based on our experience, despite the FNB was actually associated with an initial higher quadriceps strength loss, it seems not to be of enough magnitude to limit the early functionality.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of nonopioid analgesics, such as acetaminophen and cyclooxygenase 2 inhibitors, before surgery and tranexamic acid has also been shown to reduce postoperative pain and/or opioid consumption 67,68 . Regional anesthesia has been shown to improve pain management and decrease the use of opioids 69,70 . Multimodal analgesia and a procedure-specific approach have been shown to affect the limiting use of opioids substantially 61,71 .…”
Section: Team Approach: Role-specific Interventionmentioning
confidence: 99%
“…Due to the variables at play (temperature, exposure time, and nerve diameter), the block's duration is uncertain, however, it is typically measured in weeks or months. The use of cryoanalgesia in TKA is supported by scant clinical data [ 26 ]. Scientific proof and treatment regimen of postoperative pain treatment aims to give the best analgesia with the fewest side effects.…”
Section: Reviewmentioning
confidence: 99%